2009
DOI: 10.1007/s00412-009-0244-2
|View full text |Cite
|
Sign up to set email alerts
|

Re-examination of siRNA specificity questions role of PICH and Tao1 in the spindle checkpoint and identifies Mad2 as a sensitive target for small RNAs

Abstract: The DNA-dependent adenosine triphosphatase (ATPase) Plk1-interacting checkpoint helicase (PICH) has recently been implicated in spindle checkpoint (SAC) signaling (Baumann et al., Cell 128(1):101–114, 2007). Depletion of PICH by siRNA abolished the SAC and resulted in an apparently selective loss of Mad2 from kinetochores, suggesting a role for PICH in the regulation of the Mad1–Mad2 interaction. An apparent rescue of SAC functionality by overexpression of PICH in PICH-depleted cells initially seemed to confir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
66
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 62 publications
(71 citation statements)
references
References 25 publications
5
66
0
Order By: Relevance
“…Originally, it had been speculated that centromere-associated PICH might function as a tension sensor in the SAC (Baumann et al, 2007). Although a role for PICH in the SAC appears unlikely in the light of recent results (Huebner et al, 2010), a persistent connection between sister kinetochores may indeed provide a convenient platform for the placement of a tension sensor. In line with this hypothesis, centromere-associated Aurora B has recently been proposed to contribute to the monitoring of tension through its spatial separation from kinetochore-associated substrates (Liu et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Originally, it had been speculated that centromere-associated PICH might function as a tension sensor in the SAC (Baumann et al, 2007). Although a role for PICH in the SAC appears unlikely in the light of recent results (Huebner et al, 2010), a persistent connection between sister kinetochores may indeed provide a convenient platform for the placement of a tension sensor. In line with this hypothesis, centromere-associated Aurora B has recently been proposed to contribute to the monitoring of tension through its spatial separation from kinetochore-associated substrates (Liu et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Its predicted enzymatic properties and specific association with centromeres originally suggested a potential role for this protein as a tension sensor in the SAC (Baumann et al, 2007). However, in the light of recent findings, this now appears unlikely (Huebner et al, 2010;Maresca and Salmon, 2009;Uchida et al, 2009). However, the surprising discovery that PICH persisted on centromere-derived DNA during anaphase renewed interest in the role and regulation of DNA decatenation during mitotic progression .…”
Section: Introductionmentioning
confidence: 99%
“…Clearly, there is no room in this scheme for a tension-sensing kinetochore/centromere-based checkpoint element. [The recent report that after a long search this element has finally been discovered (Baumann et al 2007) was erroneous (Hubner et al 2010)]. Instead, the checkpoint detects unattached kinetochores, and the checkpoint signal is shut down at a kinetochore as MTs progressively accumulate on its surface (Rieder et al 1994;Waters et al 1998); this is a quick process (McEwen et al 1997) promoted by tension which slows the turnover rate of kinetochore-associated MTs (King and Nicklas 2000).…”
Section: The M/a Transitionmentioning
confidence: 99%
“…We had previously linked this difference to the absence of the spindle checkpoint protein Mad2 at kinetochores in siCENP-O-treated cells (McAinsh et al, 2006;McClelland et al, 2007). This difference seemed specific because it was based on two independent siRNAs for each depletion (McAinsh et al, 2006;McClelland et al, 2007); however, recent studies showed that the Mad2 mRNA is a frequent off-target for various siRNAs, raising the possibility that our siRNAs targeting CENP-O might also target Mad2 (Hubner et al, 2010;Westhorpe et al, 2010). To test for this possibility and to unequivocally confirm the specificity of our phenotypes, we generated stable HeLa cell lines expressing either siRNA-resistant EGFP-CENP-L or siRNA-resistant EGFP-CENP-O.…”
Section: Resultsmentioning
confidence: 99%